Monotherapy for toenail onychomycosis: a systematic review and network meta‐analysis. (1st February 2020) - Gupta, A.K.; Foley, K.A.; Mays, R.R.; Shear, N.H.; Piguet, V.
Summary: Background: Onychomycosis is a fungal infection of the nail caused by dermatophytes, yeasts and nondermatophyte moulds that accounts for approximately 50% of all nail‐related disease. Objectives: This study aims to assess the effectiveness and safety of monotherapy and combination treatments for toenail onychomycosis using a network meta‐analysis (NMA). Methods: Quality of evidence was assessed using Cochrane‐compliant rules and the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. Efficacy and safety outcomes were compared using a random‐effects NMA to estimate pooled odds ratios (ORs) of direct and indirect comparisons among oral and topical treatments (PROSPERO 2015: CRD42018086912). There were not enough eligible combination and device‐based therapy trials to include in the NMA. Results: Of 77 randomized controlled trials, 26 were included in the ORs (8136 patients). There were no significant inconsistencies between the direct and indirect evidence. Relative effects show that the odds of mycological cure with continuous terbinafine 250 mg or continuous itraconazole 200 mg are significantly greater than topical treatments. Fluconazole, pulse regimens of terbinafine and itraconazole, and topical treatments did not differ significantly in the odds of achieving mycological cure. The ORs of adverse events occurring with oral or topical treatments were not significantly different from each other. For mycological cure, evidence was of moderate or high quality while evidence ranged from very low to high quality for adverse events. Conclusions: Our review suggests that oral and topical treatments for toenail onychomycosis are safe and effective in producing mycological cure. What's already known about this topic? Topical treatments traditionally have lower success rates than oral treatments. Oral treatments have the advantage of shorter treatment durations, but also present challenges in cases of drug–drug interactions or immunosuppression. A network meta‐analysis (NMA) gathers data from indirect evidence to gain confidence about all treatment comparisons and allows for estimation of comparative effects that have not been investigated in head‐to‐head randomized clinical trials (RCTs). What does this study add? This NMA of efficacy and safety includes all RCTs of oral, topical, combination and device‐based treatments for toenail onychomycosis, adhering to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement for NMA. The odds of achieving mycological cure with continuous terbinafine 250 mg or continuous itraconazole 200 mg were significantly greater than topical treatments. Fluconazole, pulse regimens of terbinafine and itraconazole, and topical treatments did not differ significantly in the odds of achieving mycological cure.